Narasi sebagai Ruang Negosiasi Identitas: Analisis Poskolonial dalam Sastra Indonesia - Julian, Royyan; Sentana, Yuli Mahmudah; Hiasa, Fina (CV. ULIL ALBAB CORP, 2025)
This article examines contemporary Indonesian literature as a space for identity negotiation using a new postcolonial perspective. The research focuses on how post-1998 literary works not only represent classic colonial trauma, but also bring forth more complex identity dynamics through hybridity, third spaces, diaspora, and transculturalism. This study uses a qualitative approach to literary text analysis, examining the works of Ayu Utami (Saman), Leila S. Chudori (Pulang), Eka Kurniawan (Lelaki Harimau), and Laksmi Pamuntjak (Amba). These four works were selected because they representatively present the debate on identity in the era of reform and globalisation. The results of the study show that identity in contemporary Indonesian literature is constructed through fluid, non-linear, and dialogical narrative strategies. Saman presents the negotiation of female identity and the body as an arena of resistance; Pulang articulates diaspora identity and transnational politics; Lelaki Harimau reinterprets the relationship between violence, gender, and trauma in a local-global context; while Amba presents a space of collective memory that transcends national boundaries. Analysis shows that contemporary literature functions as a discursive arena where national and global identities are negotiated, debated, and recreated. This article contributes to the expansion of the horizon of postcolonial studies in Indonesia by shifting the focus from classical colonialism to the post-reform context. Practically, this research encourages the use of literature as a medium for multicultural identity education, cultural diplomacy, and critical reflection on Indonesia's position in the global era. Further studies are recommended to explore digital literature, diaspora literature, and interdisciplinary approaches such as digital humanities in analysing the dynamics of identity in contemporary Indonesian literature.